Farmers' perceptions, existing knowledge and current control methods of major stored maize grain insect pests in West Showa, Ethiopia. (14th December 2021) - Megerssa, Martha; Negeri, Mulugeta; Getu, Emana; Demissie, Girma; Selvaraj, Thangavel
ABSTRACTS: Maize is one of Ethiopia's most important and strategic staple food security crops, grown by smallholder farmers. However, Maize production has not reached maximum potential due to a number of constraints, including storage insect pests, resulting in both qualitative and quantitative losses. The aim of this research was to assess farmers' perceptions and understanding of major maize grain storage insect pests, investigate farmers' current pest management activities, and identify pest management challenges as well as key intervention areas in the development of IPM strategies for maize grain storage pests. From February to April 2018, a survey was conducted in Ethiopia's Ambo and Tokke kuttayye districts of the West Showa Administrative Zone. Face-to-face interviews with 146 randomly selected farmer household respondents were conducted using a semi-structured questionnaire. A large percentage of the farmers interviewed in both districts grew hybrid maize varieties. The majority of farmers (65.7%) packed their maize grain in polypropylene bags. Traditional storage facilities were used by just around a quarter of them. The majority of farmers kept their maize grain shelled, while a small percentage kept it unshelled. Most of the respondents knew about storage insect pests and reported that in the storage, their maize grains were attacked by a variety of insect pests, causing estimated damage of 26–50%, among which, Maize weevil ( Sitophilus zeamais Motschulsky) and Angoumois grain moth ( Sitotroga cerealella Olivier) were the most common ones. Age and storage form had a positive and statistically significant impact on farmers' perception of severe insect pest attack on stored maize. Respondents used a number of control approaches, the most common of which was the use of synthetic pesticides. While, traditional control methods were only used rarely. In general, the results highlighted the importance of combining resistant varieties, pesticidal plants, and cultural pest management methods to establish effective IPM approaches, as well as addressing the challenges that prevent the use of modern storage technologies and control methods.